Quality By Design: Approach to Analytical Method Validation (Sciences of Pharmacy, 2022)
A pharmaceutical industry is highly regulated by a quality policy in its management. The principles of Quality by Design (QbD) must be applied to ensure the development of pragmatic and systematic methods while managing the risks associated with analytical methods. Quality by Design (QbD) is a scientific way to develop easy and robust analytical techniques for critical analysis. Quality by Design (QbD) is a systematic approach to product or method development that starts with predetermined goals and uses a science and risk management approach to achieve product and method understanding. The concept of risk management is deeply integrated into the quality assurance system to ensure pharmaceutical quality and patient safety. In the context of quality control, detecting impurities in raw materials and finished products is a major concern. Analytical Quality by Design (AQbD) aims to achieve quality in measurement. The main objectives are to explain the various steps involved in developing a method using a Quality by Design (QbD) approach for the development of analytical methods and to explain the implementation of Quality by Design (QbD) in the validation of analytical procedures. The advantages of applying Quality by Design (QbD) principles to analytical techniques include finding and minimizing sources of variability that could lead to poor method robustness and ensuring that the method meets the desired performance requirements over the product and method life cycle. The Analytical Quality by Design (AQbD) strategy is increasingly being adopted as it allows an early understanding of the method and guarantees the determination of a wider set of experimental conditions.